Human Tendon Stem/Progenitor Cell Features and Functionality Are Highly Influenced by in vitro Culture Conditions - Perucca Orfei, Carlotta; Bowles, Annie C; Kouroupis, Dimitrios; Willman, Melissa A; Ragni, Enrico; Kaplan, Lee D; Best, Thomas M; Correa, Diego; de Girolamo, Laura (Frontiers in Bioengineering and Biotechnology, 2021)
Our understanding of tendon biology continues to evolve, thus leading to opportunities for developing novel, evidence-based effective therapies for the treatment of tendon disorders. Implementing the knowledge of tendon stem/progenitor cells (TSPCs) and assessing their potential in enhancing tendon repair could fill an important gap in this regard. We described different molecular and phenotypic profile of TSPCs modulated by culture-density, as well as their multipotency and secretory activities. Moreover, in the same experimental setting, we evaluated for possible difference responses to inflammatory stimuli mediated by TNFα and IFNγ. We also preliminarily investigated their immunomodulatory activity and their role in regulating degradation of Substance P. Our findings indicated that TSPCs cultured at low-density (LD) exhibited cobble-stone morphology and a reduced propensity to differentiate. A distinctive immunophenotypic profile was also observed with high secretory and immunomodulatory responses when primed with TNFα and IFNγ. In contrast, TSPCs cultured at high density (HD) showed a more elongated fibroblast-like morphology, a greater multi-differentiation potential, and a higher expression of tendon-related genes with respect to LD. Finally, HD TSPCs showed a lower immunomodulatory response when primed with TNFα and IFNγ. A shift from low-to-high culture-density during TSPC expansion demonstrated intermediate features confirming the cellular adaptability of TSPCs. Taken together, these experiments allowed us to identify relevant differences in TSPCs based on culture conditions. This ability of TSPCs to acquire distinguished morphology, phenotype, gene expression profile and functional response advances our current understanding of tendons at a cellular level and suggest responsivity to cues in their in situ microenvironment.